The Role of Human Development in Improving Local Government Performance Through Good Government Governance - Sunardi, Sunardi; Djazuli, Abid; Handayani, Risma Dwi; Hidayat, Bachtari Alam; Saksono, Herie (Research and Development Agency Ministry of Home Affairs, 2022)
The quality of audit opinion results of local government financial statements in 2015 – 2020 has increased. Still, non-compliance with laws and corruption cases has increased, indicating that the implementation of Good Government Governance (GGG) has not gone well. This paper provides empirical evidence of the role of human development in realizing GGG and its effect on the performance of local governments in Indonesia. The research was designed as associative quantitative research, an organizational unit of analysis. The total population is the regency and city government in Indonesia, as many as 514 local governments, and the sampling technique is purposive sampling. The qualified samples were 268 local governments, with data observed from 2018 to 2020, or 3 years, so the number was 804. The data was sourced from the Regional Government Implementation Performance Evaluation report. The GGG variables were measured using indices and local government performance variables use scores. The main analysis uses SEM PLS and additional analysis with panel regression. The results showed that GGG had a significant effect on the performance of local governments. Novelty, the dimension of human development can strengthen the GGG variable so that its influence on the performance of local governments is even greater. This research has theoretical, managerial, policy, and practical implications. In addition, the completeness of the research data, which is still lacking in information, is a limitation of this study. Furthermore, recommendations for local governments so that human development receives special attention to increasing competitiveness by increasing the allocation of labor budgets.